Fruit fly phylogeny imprints bacterial gut microbiota. (3rd May 2022) - Ravigné, Virginie; Becker, Nathalie; Massol, François; Guichoux, Erwan; Boury, Christophe; Mahé, Frédéric; Facon, Benoit
Abstract: One promising avenue for reconciling the goals of crop production and ecosystem preservation consists in the manipulation of beneficial biotic interactions, such as between insects and microbes. Insect gut microbiota can affect host fitness by contributing to development, host immunity, nutrition, or behavior. However, the determinants of gut microbiota composition and structure, including host phylogeny and host ecology, remain poorly known. Here, we used a well‐studied community of eight sympatric fruit fly species to test the contributions of fly phylogeny, fly specialization, and fly sampling environment on the composition and structure of bacterial gut microbiota. Comprising both specialists and generalists, these species belong to five genera from to two tribes of the Tephritidae family. For each fly species, one field and one laboratory samples were studied. Bacterial inventories to the genus level were produced using 16S metabarcoding with the Oxford Nanopore Technology. Sample bacterial compositions were analyzed with recent network‐based clustering techniques. Whereas gut microbiota were dominated by the Enterobacteriaceae family in all samples, microbial profiles varied across samples, mainly in relation to fly identity and sampling environment. Alpha diversity varied across samples and was higher in the Dacinae tribe than in the Ceratitinae tribe. Network analyses allowed grouping samples according to their microbial profiles. The resulting groups were very congruent with fly phylogeny, with a significant modulation of sampling environment, and with a very low impact of fly specialization. Such a strong imprint of host phylogeny in sympatric fly species, some of which share much of their host plants, suggests important control of fruit flies on their gut microbiota through vertical transmission and/or intense filtering of environmental bacteria.